Activated protein C attenuates pulmonary coagulopathy in patients with acute respiratory distress syndrome. Issue 5 (15th May 2013) - Cornet, A. D.; Hofstra, J. J.; Vlaar, A. P.; Tuinman, P. R.; Levi, M.; Girbes, A. R.; Schultz, M. J.; Groeneveld, A. B.; Beishuizen, A.
Summary Objective Acute respiratory distress syndrome (ARDS) frequently complicates critical illness. We hypothesized that an infusion of recombinant human activated protein C (rh‐APC), a natural anticoagulant, would attenuate pulmonary coagulopathy and injury. Methods In this sub study of a multicenter open‐label randomized controlled trial of patients with ARDS, we compared an intravenous (i.v.) infusion of rh‐APC (24 mcg kg−1 h−1 for 96 h) with placebo. Patients with sepsis or septic shock were excluded. Results In 27 patients serial non‐directed bronchoalveolar lavage fluid (NBLF) samples were obtained: 16 patients were treated with rh‐APC and 11 patients with placebo. The rh‐APC infusion was associated with higher APC levels in plasma during the infusion period of 4 days (P = 0.001), as well as higher APC levels in NBLF up to day 5 after the start of the infusion (P = 0.028). An infusion of rh‐APC was associated with lower levels of thrombin–antithrombin complexes (P = 0.009) and soluble tissue factor (P = 0.011) in NBLF, compared with treatment with placebo. An infusion of rh‐APC affected fibrinolysis, as plasminogen activator activity levels in NBLF were higher in the patients treated with rh‐APC (P = 0.01), presumably as a result of lower NBLF levels of plasminogen activator inhibitor 1, (P = 0.01). The rh‐APC infusion decreased the lung injury score (P = 0.005) and simplified the acute physiology score (P = 0.013) on day 5, when compared with baseline. The rh‐APC infusion was not associated with bleeding complications. Conclusion An infusion of rh‐APC in patients with ARDS attenuates pulmonary coagulopathy and injury.